Indication and uses of temporary anchorage device in orthodontic - Bawyan, Rehab Fuad; Anzi, Sarah Khalid Al; Alkhadra, Noha Basil; Alkhaier, Nur Ali Alhaies; Alsemran, Ohood Mohammad; Ghulam, Abdulaziz Nizar; Nahari, Nada Mohammed; Alnami, Abdulelah Ahmed; Alnami, Abdulelah Ahmed; Alshahrani, Raghad Saeed; Alqurashi, Salman Fahad; Alshammari, Alanood Monawer (International Journal Of Community Medicine And Public Health, 2021)
Treating various types of malocclusion is dependant on providing a secure anchorage. In this context, it has been shown that teeth, intramaxillary, and/or extraoral appliances are required to achieve favorable outcomes regarding anchorage treatment. A Temporary anchorage device (TAD) has been introduced in the literature in this context. It has been described as a temporary device that can be used after completing treatment. The aim of the study was to review the indications and uses of TADs in orthodontic treatment. The current evidence shows that introducing TADs in the field of orthodontic treatment has been associated with favorable outcomes that encountered the previous multiple challenges reported with the conventional anchorage approaches. Contemporary orthodontic settings reported various uses for TADs, including corrections in transverse, vertical, and anteroposterior dimensions. Combined use of TADs and conventional approaches were also evaluated with favorable outcomes. These findings indicate the validity of TADs in orthodontic treatment and call for its future implications and clinical applications. However, it should be noted that post-treatment evaluation on a long-term basis was not adequately reported in the current literature, indicating the need for future investigations for further validation.